Formulasi dan Uji Stabilitas Fisik Sediaan Gel Ekstrak Etanol Daun Rambutan (Nephelium Lappaceum L.) - Astriani, Andi Dian; Fitriani, Ana; Pakki, Ermina (Journal of Pharmaceutical and Health Research, 2023)
The ethanol extract of rambutan leaves has anti-Staphylococcus aureus properties. The purpose of this investigation is to formulate the ethanol extract of rambutan leaves (Nephelium lappaceum L.) in order to determine the stable concentration of carbopol 940 for gel preparations. The extraction technique utilised was maceration with 96% ethanol. Formula 1 (0.7% carbopol 940), Formula 2 (0.9% carbopol 940), and Formula 3 (1.1% carbopol 940) were developed for the gel preparation formulation. Organoleptic assays, homogeneity, spreadability, pH, and adhesion were conducted before and after accelerated storage at 400°C and 75% relative humidity. The results of the organoleptic test revealed that preparations F1, F2, and F3 had a semi-solid consistency, a dark brown hue, and a distinct extract odour, and that they were homogeneous. Before accelerated conditions, the spreadability test yielded Farmula 1 (6,3 cm), Farmula 2 (5,96 cm), and Farmula 3 (5.3 cm). After accelerated conditions, the results were F1 (5.86cm), F2 (5.43cm), and F3 (5.16cm). Before the accelerated condition, the pH test results were F1 (5.54), F2 (5.91), and F3 (6.00). After the accelerated condition, the results were F1 (6.43), F2 (6.08), and F3 (5.76). The adhesion test before the accelerated condition yielded F1 (4.37 seconds), F2 (4.28 seconds), and F3 (4.45 seconds), and after the accelerated condition yielded F1 (4.57 seconds), F2 (4.38 seconds), and F3 (4.66 seconds of data, it can be concluded that the gel formulation of rambutan leaf extract from various concentrations of 0.7%, 0.9%, and 1.1% carbopol 940 is physically stable.